PERSEPSI MAHASISWA JURUSAN MANAJEMEN TERHADAP MATA KULIAH ETIKA BISNIS - Murwartiningsih, - (Dinamika Pendidikan, 2009)
The purposes of the research were to identify the differences between Private students of Management from State University and Private University perceptions toward the importance of business ethics and to identify the adequate of ethic coverage in management curriculum. Dimension of business ethical studied here were autonomy, honesty, justice, mutuality and high moral integrity. The samples were consisted of 150 students of management from State University and 150 students of management from Private University in Semarang. Research method used was survey one using questionnaires. Hypothesis test used independent sample T-test. Research result found that there was significant development between students from State University and Private University toward business ethics. Students of management from State University had better ethic perceptions than students from Private University had. Based on result of forum discussion about coverage of ethic content in curriculum of management education, most respondents stated that the curriculum was not adequate that it should be integrated with certain subjects. Key words: perception, business ethics, coverage of ethical contents